Characterizing 5-hydroxymethylcytosine in human prefrontal cortex at single base resolution - Gross, Jeffrey A.; Pacis, Alain; Chen, Gary G.; Barreiro, Luis B.; Ernst, Carl; Turecki, Gustavo (BMC genomics, 2015)
The recent discovery that methylated cytosines are converted to 5-hydroxymethylated cytosines (5hmC) by the family of ten-eleven translocation enzymes has sparked significant interest on the genomic location, the abundance in different tissues, the putative functions, and the stability of this epigenetic mark. 5hmC plays a key role in the brain, where it is particularly abundant and dynamic during development. Here, we comprehensively characterize 5hmC in the prefrontal cortices of 24 subjects. We show that, although there is inter-individual variability in 5hmC content among unrelated individuals, approximately 8 % of all CpGs on autosomal chromosomes contain 5hmC, while sex chromosomes contain far less. Our data also provide evidence suggesting that 5hmC has transcriptional regulatory properties, as the density of 5hmC was highest in enhancer regions and within exons. Furthermore, we link increased 5hmC density to histone modification binding sites, to the gene bodies of actively transcribed genes, and to exon-intron boundaries. Finally, we provide several genomic regions of interest that contain gender-specific 5hmC. Collectively, these results present an important reference for the growing number of studies that are interested in the investigation of the role of 5hmC in brain and mental disorders.